Insight in thermomechanical constitutive modeling of shape memory polymers - Shojaei, Amir; Xu, Wei; Yan, Cheng; Yang, Qianxi; Li, Guoqiang (Frontiers in Mechanical Engineering, 2022)
Shape memory polymers (SMPs) are a new member of the smart materials family. SMPs have found wide applications or potential applications in almost all manmade structures and devices. In order to better design smart structures and devices using SMPs, thermomechanical constitutive modeling is essential. In this insight paper, we will focus on presenting several multi-length-scale and multi-physics modeling frameworks, including thermodynamics consistent model, elasto-viscoplastic model, statistical mechanics model, and phase evaluation law model. The SMPs modeled will include amorphous one-way shape memory polymers, semicrystalline one-way shape memory polymers, semicrystalline two-way shape memory polymers, and functional and mechanical damage effect on SMPs. Finally, we will give some in-depth perspectives on future development in this area of study.